Redesain Gedung Juang 45 Tambun Sebagai Obyek Pariwisata Kesejarahan Di Bekasi (Berbasis Ummatan Wasathan Wa Khairu Ummatin) - Aditama, Yahya Wido, Ir. Nurhasan, MT (2016)
Bekasi community who had become industrialized societies certainly brought changes to the behavior of society. Besides the positive changes, There are also changes in negative behavior such as individualistic attitude, apathy, until the lost of adab. Gedung Juang 45 Tambun condition as a cultural heritage that is poorly maintained also into the background of redesign. This redesign using the approach of Islamic Architecture through paradigm of the Quran, as initiated by Kuntowijoyo. also using the method participatory action to obtain agreement among the three elements of the user. conservation measures using the method of preservation and revitalization. heritage preservation is an endeavour that seeks to preserve, conserve and protect buildings, objects, landscapes or other artifacts of historical significance. Revitalization is the activity of the restoration that specifically targeted to obtain optimum added value in economic, social and cultural in the use of buildings and environmental heritage. Through the paradigm of of the Quran, found the concept of Ummatan Wasathan and Khoiru Ummah as a concept of an ideal society to answer the problem of the industrialized societies in Bekasi. The derivation effort conducted of the abstract values which contained in the concept of an ideal society toward architectural strategy, then converted into a real spatial form. The results obtained in the form of spaces of museums, cultural performances or amphitheaters room, gathering room, an office manager, etc. Beside spatial forms are included in the category of physical design, the design also obtained non-physical such as regulations, the results of participatory dialogue.